PENGETAHUAN KADER TENTANG TANDA RISIKO TINGGI PADA IBU HAMIL - Roekmy Prabarini Ario (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2016)
One of the causes of high maternal mortality rate is a pregnancy complication that can arise through the danger signs of pregnancy. Knowledge cadres in recognizing danger signs can be one of the determinants of pregnancy care to prevent complications. This study aimed to determine the knowledge of cadres of the telltale signs of high risk pregnant women in sub Sumberejo Village District of Banyuputih Situbondo Year 2015. This study was a descriptive technique with the type of cross-sectional design. The population in this study adalan all cadres who are in the village clinics Sumberejo many as 55 people. Data retrieval technique with a closed questionnaire instrument. Results of research in getting from 55 respondents who have a good knowledge of most of that 32 respondents (58%), a small portion pengtahuaanya enough that 13 respondents (24%). And there is a small portion of 10 respondents (18%) were less knowledge about the sign -sign high risk pregnant women, and by the age of 31-40 years nearly half of 20 respondents (36.4%) were knowledgeable good, based on elementary education is almost half of that 16 respondents (29.1%) good knowledge, based on the information obtained by respondents from the majority of health workers is 32 respondents (58.2%) were knowledgeable good, and based on the experience of nearly setegahnya ie 24 respondents (43.63%) knowledgeable good. The conclusion of this study was largely cadres know and understand about the importance of early detection of signs of high- risk pregnant women, and it is expected for the midwifery profession to further enhance the knowledge of cadres of the signs of high risk pregnant women. Keywords: Knowledge, Kader, Signs of High Risk in pregnant women. ABSTRAK Pengetahuan kader dalam mengenali tanda bahaya dapat menjadi salah satu penentu perawatan kehamilan untuk mencegah komplikasi. Penelitian ini bertujuan untuk mengetahui pengetahuan kader tentang tanda-tanda risiko tinggi pada ibu hamil di Pustu Desa Sumberejo Kecamatan Banyuputih Kabupaten Situbondo Tahun 2015. Desain penelitian ini adalah tehnik Deskriptif dengan jenis rancangan Cross sectional. Populasi dalam penelitian ini adalan semua kader yang berada di pustu desa sumberejo sebanyak 55 orang. Tehnik pengambilan data dengan instrumen kuesioner tertutup. Hasil penelitian di dapatkan dari 55 responden yang memiliki pengetahuan baik sebagian besar yaitu 32 responden (58%), sebagian kecil yang pengtahuaanya cukup yaitu 13 responden (24%). dan terdapat sebagian kecil yaitu 10 responden (18%) yang pengetahuannya kurang. dan responden yang berpengetahuan baik berdasarkan usia 31-40 tahun hampir setengahnya yaitu 20 responden (36,4%), berdasarkan pendidikan SD hampir setengahnya yaitu 16 responden (29,1%), berdasarkan informasi yang didapatkan oleh responden dari tenaga kesehatan sebagian besar yaitu 32 responden (58,2%), dan berdasarkan pengalaman hampir setegahnya yaitu 24 responden (43,63%). Kata Kunci : Pengetahuan, Kader, Tanda-Tanda Risiko Tinggi pada ibu hamil.